Sporadic Pemphigus Foliaceus in a 3-Year-Old Vietnamese Girl: A Case Report and Literature Review - Trinh Thi Diem Nguyen; Trinh Ngoc To Chau; Phuong Thi Doan Vo; Hao Trong Nguyen (Hindawi Limited, 2024)
Pemphigus foliaceus is an uncommon autoimmune intraepidermal blistering disease characterized by immunoglobulin (Ig) G autoantibodies that attack desmoglein-1 in the epidermis. There are two predominant forms of pemphigus foliaceus, sporadic and endemic. Sporadic pemphigus foliaceus is known to be more prevalent in middle-aged and elderly people and to be extremely rare in children. Less than 40 nonendemic pediatric pemphigus foliaceus cases have been documented in the literature. This report documents a case of sporadic pemphigus foliaceus in a 3-year-old Vietnamese girl who presented with generalized scaling and crusted erosions over the body.